Differences in the levels of physical fitness of individuals with moderate Intellectual Disabilities participating and not participating in school-based physical activities - Yilmaz, Atike; Mirze, Fatih (Citta Aperta Edizioni Srl, 2022)
In Turkey individuals with intellectual disabilities, receiving supportive education services, are provided with individual and/or group training in Special Education and Rehabilitation Centers for a maximum of 8 lessons per month and 3 lessons per day. However, games, sports and physical activity classes are not conducted in these centers. In the tier-1 Special Education Application Center, which is the other educational institution where we conducted our study, games, sports and physical activity lessons are, instead, carried out three hours a week. This study aims to examine the differences in the levels of physical fitness of individuals with moderate intellectual disabilities participating and not participating in school-based physical activities. This study uses the causal-comparative research method. The participants of this study were 32 students with moderate intellectual disability who were educated at the Mud Special Education Application Center (n = 16) and at Special Education and Rehabilitation Centers (n = 16). Body Mass Index (BMI), flexibility, sitting height, arm span, standing long jump, and the throwing distance of the medicine ball of the participants were measured and the two groups were compared between each other. The Mann-Whitney U test was used for the independent comparison of the measured scores of the study. While the research findings revealed a statistically significant difference in favor of students who were educated at the Mus Special Education Application Center in terms of the variable measuring flexibility (p < .05), no statistically significant difference was found between the two groups in terms of BMI, standing long jump, sitting height, arm span, and the medicine ball throwing variables (p > .05). The results of the study show that the levels of physical fitness in students attending the Mus Special Education Application Center are better. It is thus recommended to implement school-based physical activity practices to increase the levels of physical fitness in students attending special education and rehabilitation centers.
Keywords: Moderate Intellectual Disabilities; Physical Activity; Physical Fitness